Case Report: Dramatic Response to Crizotinib in a Patient With Non-Small Cell Lung Cancer Positive for a Novel ARL1-MET Fusion - Ma, Qing; Kong, Lingping; Zhong, Diansheng (Frontiers in Oncology, 2022)
It is imperative to know the status of oncogenic drivers in patients with non-small cell lung cancer (NSCLC). Compared with ALK and ROS1 fusion, MET fusion is relatively rare in NSCLC. In this case, we report the case of a female patient with NSCLC positive for a novel ARL1-MET fusion. The patient achieved about a five-month progression-free survival (PFS) after receiving crizotinib for unresectable right lung malignancies. To the best of our knowledge, this case provides the first clinical evidence that the novel ARL1-MET fusion might be an actionable mutation in NSCLC.